EVALUASI STRATEGI PT XL AXIATA, TBK DALAM MENGHADAPI PERSAINGAN INDUSTRI PADA ERA MOBILE DATA SERVICE (MDS) - , Mahendra Kurniawan, Dr. Bambang Riyanto L.S, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nowadays. Indonesiaâs telecommunication industry is in maturity condition. In fact, there are difficulties in its member to grap revenue growth despite the increment of its subscriber. The advance of internet technology or Mobile Data Service (MDS) already gives an opportunity to telecommunication companies to increase their revenue. The question is whether XL Axiata able to exploit the advantages of this condition with their current strategy? The main purpose of this research is to evaluate the current strategy of XL Axiata, to analize the internal environment of the company and external environment of Indonesiaâs telecommunication industry, so we can get conclusion whether the companyâs strategy is still adequate to implemented in Mobile Data Service (MDS) era and give us alternative strategy to improve the companyâs competitive ability in Indonesia telecommunication industry. To evaluate how well is the companyâs present strategy working, indicator such as sales increment, subscriber growth compared with their rival, until how good is the companyâs brand image is used. The internal strength and weakness analysis is used to capturing best opportunity and defends against the threat, so the company can crafting good strategy that capitalizes on companyâs resources. The External analysis such as economic dominant feature, Porter five forces of competition, driving forces analysis, Key Success Factor analysis and Strategic Group Map, is used to maximize companyâs opportunity, minimize companyâs threat and increase the opportunity to win the competition in industry.